Relationship Between Pregnant Women's Anxiety Levels and Baby Blues Syndrome During the Postpartum Period - Rikhaniarti, Tri; Irmadani, Andi Syarifa; Ernawati, Ernawati (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to explore the relationship between the level of anxiety in pregnant women and the incidence of baby blues syndrome during the postpartum period. The primary focus is to understand the psychological and physiological mechanisms underlying the transition from prenatal anxiety to postpartum emotional disorders. Research Method: This study employs a qualitative approach, incorporating a systematic literature review of scientific articles published between 2015 and 2025. The analysis was conducted on secondary data from national and international journals, considering the psychosocial, hormonal, and neurobiological frameworks related to anxiety in pregnant women and baby blues. Results and Discussion: Findings indicate that anxiety during pregnancy is significantly correlated with an increased risk of postpartum baby blues syndrome. Factors such as lack of social support, cultural pressure on the role of mothers, and hormonal fluctuations contribute to the occurrence of emotional disturbances after childbirth. This study also confirms that emotional unpreparedness during pregnancy is an important indicator of mental stability in mothers during the postpartum period. Implications: The results of this study suggest the need for anxiety screening in antenatal services, training for healthcare workers in the early detection of emotional disorders, and strengthening psychosocial interventions as preventive measures. These findings also encourage the development of more holistic maternal mental health policies.